Effects of Self-Care Education Intervention Program (SCEIP) on Activation Level, Psychological Distress, and Treatment-Related Information - Nor Aziyan, Yahaya; Khatijah Lim, Abdullah *; Vimala, Ramoo; Nor Zuraida, Zainal; Wong, Li Ping; Danaee, Mahmoud (MDPI, 2022)
Self-care education can direct patients to manage their side effects during treatment, reduce psychological distress, and improve self-care information. In this study, the effectiveness of the Self-Care Education Intervention Program (SCEIP) on patient activation levels, psychological distress, and treatment-related concerns in women with breast cancer was assessed by adopting a longitudinal quasi-experimental pre-test and post-test design. The data for 246 women with breast cancer undergoing adjuvant chemotherapy were collected. Pre- and post-interventional assessments were conducted at baseline (T1) and the second (T2), fourth (T3), and sixth (T4) cycles using the 13-item Patient Activation Measure, 14-item Hospital Anxiety and Depression Scale, and 25-item Cancer Treatment Survey. It was found that the SCEIP significantly improved the activation level (p ≤ 0.001), psychological distress (anxiety level (p ≤ 0.001), the depression level (p ≤ 0.001)), and treatment-related concerns (sensory/psychological concerns (p = 0.05); procedural concerns (p ≤ 0.001)). Therefore, the SCEIP could potentially improve patients' activation level, psychological distress, and treatment-related concerns regarding symptom management during chemotherapy, specifically for Malaysian women with breast cancer.